Attachment of the floating charge in Scots law - MacPherson, Alisdair (The University of Edinburgh, 2018)
This thesis examines the attachment of the floating charge to property in Scots law. The work is divided into two main parts. The first part focuses on how the charge interacts with property in a general sense. The second part considers attachment and its consequences in relation to the regimes for particular types of property. It is contended that the floating charge does not directly affect property prior to attachment. And even upon attachment its status as a “real right” is questionable. This is primarily because the charge is patrimonially limited by its enforcement mechanisms. It can only be enforced through a liquidator, receiver or administrator, and the powers of these parties are seemingly confined to property in the chargor’s estate. The thesis also demonstrates that ownership is a useful tool for examining what is required for a charge to attach to property. The most suitable approach is for ownership by the chargor to be both necessary and sufficient for attachment, but this is not the case under the present law, at least for certain property and transactions. Other currently prevailing views regarding the charge’s attachment are also challenged. This includes the belief that the charge attaches as if it is the relevant form of security for the property in question. Instead, it is suggested that the charge should be considered to attach as a “sui generis” fixed security. In addition, there are a range of difficulties that arise when the charge’s attachment and ranking are considered alongside the rules of transfer and security for specific property types. Uncertainty in the background law, and failure to take account of this when the charge was introduced, and subsequently, has meant that the charge may not operate effectively when, for example, property has been transferred for security purposes. All of this is explored in detail in the second part of the thesis.
The attachment of the floating charge in Scots law
Keywords: floating charge; Scots law